(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This study, entitled “The Impact of Rijāl Methodologies in the Imami and Sunni Schools on the Authority of Authentic Hadith: A Comparative Study,” aims to examine the role of Rijāl science in evaluating hadith narrations and to analyze how methodological differences between the two schools affect the acceptance or rejection of authentic hadith. Rijāl science is considered one of the fundamental disciplines concerned with investigating the reliability, integrity, and credibility of narrators in order to distinguish between authentic and weak hadiths. As such, it represents a central tool in both jurisprudential and theological deduction.